1995
DOI: 10.1093/intqhc/7.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Utilization Review Program in Portugal

Abstract: This paper describes the work that has been under way in the Portuguese government hospital sector, with respect to the use of an adapted version of the Appropriateness Evaluation Protocol (AEP). Modifications to the original system were determined through a series of experiments at pilot hospitals and reliability and user profile studies were subsequently conducted using the modified criteria. Results were of great value in terms of the identification and quantification of problems. On average, approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 0 publications
1
8
1
2
Order By: Relevance
“…This study reported a 12% rate of inappropriate hospitalization use, which falls within the 5% to 74% [18,[20][21][22][23][24][25][26] ranges reported in literature.…”
Section: Discussionsupporting
confidence: 66%
“…This study reported a 12% rate of inappropriate hospitalization use, which falls within the 5% to 74% [18,[20][21][22][23][24][25][26] ranges reported in literature.…”
Section: Discussionsupporting
confidence: 66%
“…effective biomedical technological resources have been utilized in situations in which these resources are not indicated from the strictly medical point of view (7). In the United States, it has been described that there is an inappropriate hospitalization use in elderly population of between 18% and 50% (8), and of between 10% and 74% in the European Union (EU) (8–13).…”
Section: Introductionmentioning
confidence: 99%
“…An ‘inappropriate hospital admission’ can be defined as an admission that does not result in any significant benefit for the patient, or which results in benefit which could have been obtained at a lower care level. Studies from different countries have almost invariably found high rates of such admissions, with most reported percentages in the range of 10–25 [1–8]. One reason for the interest in inappropriate admissions has been the belief that they represent a potential for proportional cost reductions.…”
Section: Introductionmentioning
confidence: 99%